2000
DOI: 10.1007/pl00007265
|View full text |Cite
|
Sign up to set email alerts
|

Optimal therapeutic range for oral anticoagulants in Japanese patients with prosthetic heart valves: a preliminary report from a single institution using conversion from thrombotest to PT-INR

Abstract: The thrombotest (TT) technique has been widely used in Japan for monitoring oral anticoagulant therapy (OAT). The therapeutic range was originally recommended to be 10%-25%. However, the International Committee for Standardization in Hematology/International Committee on Thrombosis and Hemostasis (ICSH/ICTH) recommended using the international normalized ratio of prothrombin time (PT-INR) for monitoring OAT. It is necessarv to use a universal standard measure for monitoring OAT in accordance with the ICSH/ISTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Mori et al [6] studied 102 Japanese patients with mechanical heart valve prosthesis and found a significant increase in morbidity from bleeding with an INR >2.5. Uetsuka et al [7] studied 1,157 Japanese patients receiving warfarin therapy after prosthetic valve replacement during a mean follow-up period of 2.44 years and found that the incidence of TEs did not increase with a lower INR of 1.5. Therefore, they suggested that the incidence of TEs is lower in Japan, despite a less intensive regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Mori et al [6] studied 102 Japanese patients with mechanical heart valve prosthesis and found a significant increase in morbidity from bleeding with an INR >2.5. Uetsuka et al [7] studied 1,157 Japanese patients receiving warfarin therapy after prosthetic valve replacement during a mean follow-up period of 2.44 years and found that the incidence of TEs did not increase with a lower INR of 1.5. Therefore, they suggested that the incidence of TEs is lower in Japan, despite a less intensive regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are racial differences in warfarin control after mechanical valve replacement, careful evaluation of the results in Japanese patients must be considered (3–5). Also, careful monitoring according to the prothrombin time‐international normalized ratio (PT‐INR) by integrating conflicting risks of bleeding and thromboembolism is necessary.…”
Section: Valvular Heart Diseasementioning
confidence: 99%
“…PT‐INR levels as indices of anticoagulation therapy for patients with prosthetic valves are maintained in a lower range in Japan than in North America and Europe because of particular concerns about bleeding complications, but good results free from thromboembolic complications have been reported (24,25). Our target INR level is slightly lower than that of the guideline set by the Japanese Circulation Society in 2004 (ranging from 2.0 to 3.0) because higher incidence of serious bleeding complications in Japanese patients is reported (24,25,30). However, the follow‐up for these patients was excellent because 80% of them ranged in the optimal therapeutic value of the PT‐INR (31).…”
Section: Discussionmentioning
confidence: 99%
“…Their postoperative anticoagulation level was maintained at the PT‐INR ranging from 1.6 to 2.5 in relation to the control level, using warfarin and an antiplatelet agent administered every month by family doctors (24,25). For double valve replacement and atrial fibrillation, a higher intensity of PT‐INR (2.0–3.0) was maintained.…”
Section: Methodsmentioning
confidence: 99%